POLA PEMBELAJARANPENDIDIKAN ILMU PENGETAHUAN SOSIAL BERBASIS KEARIFAN LOKAL DI KELAS IVSEKOLAH DASAR NEGERI 04 BUANTAN BESAR KECAMATAN SIAK KABUPATEN SIAK - Noviana, Eddy; Erlisnawati, Erlisnawati; Bakri, Rifka Mahira (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2014)
Learning social science education gives a chance to give some attentions to care and usesurrounding area. Emperical fact in learning social science education before a teacher is onlyperson who gives information that is called teacher centered. Learning materials used focusesinto text books (material in the text books does not adopt and relate into local superiority andwisdom)This research only focuses into development of teaching material of learning socialscience education which has primary school local wisdom basis into competence standart andbasic standart in the first semester of grade IV.This research aims to develop teachingmaterial of learning social science education in Primary School based on local wisdom basiswhich can be used as a reference or supplement by teachers and studetns in learning.Themothod used is research and development design. This research is done into four steps that is1) study literature, 2) research plan, 3) research development, and 4) implementation. Datacollection technique used in this research is using interview, questionnaire, observation,documentations, and test. Meanwhile, triangulation technique and simple statistics are used toanalyze the data. The research showed that 1) teaching materials of of learning social scienceeducation based on local wisdom helps teachers in developing and relating learning materialsin learning social science education with potential of local area especially Siak regency, andb)khususnya di Kabupaten Siak; dan (b) teaching materials of of learning social scienceeducation based on local wisdom helps students to understand potential and condition ofsurrounding area. It is proven by increasing students’ understanding in learning learningsocial science education based on local wisdom from average score in pretest 31,73 into53,85 in posttest within increasing average score 0,33 in fair category.Keywords: local wisdom, and social science education